Letter from Edward J. Nolan to Margaret M. Booth - Nolan, Edward J. (1888)
Edward J. Nolan, recording secretary of the Academy of Natural Sciences, writes to Margaret M. Booth née Cardeza to inform her of her late husband, James Curtis Booth (1810-1888)'s, date of election to the academy.
Keywords: Booth, James Curtis, 1810-1888; Academy of Natural Sciences of Philadelphia; Martinez Cardeza, Margaret